2023
DOI: 10.1162/glep_a_00702
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, and the Case for Intersectional Water Security

Abstract: This Forum article reports on a meta-review of more than 19,000 published works on water security, of which less than 1 percent explicitly focus on race or ethnicity. This is deeply concerning, because it indicates that race and ethnicity—crucial factors that affect the provision of safe, reliable water—continue to be ignored in academic and policy literatures. In response to this finding the Forum calls for building intersectional water security frameworks that recognize how empirical drivers of social and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…While drawing a causal relationship between race and water insecurity is not within the scope of this research, the 2020 UN World Water Report does explicitly relate water insecurity and intersectionality, especially regarding race and class ( UN Water, 2020). Peer-reviewed studies on this issue, however, overwhelmingly exist in the North American context (e.g., Deitz and Meehan, 2019;Dickin and Gabrielsson, 2023;Harrington et al, 2023;Meńdez-Barrientos et al, 2023;Workman and Shah, 2023). For example, a spatial analysis of water insecurity across the United States by Deitz and Meehan (2019) found that deficiencies in household water infrastructure are concentrated in regions typically inhabited by racialized groups.…”
Section: The Role Of Colonialism and Race In Marine Ecotourism And Wa...mentioning
confidence: 99%
“…While drawing a causal relationship between race and water insecurity is not within the scope of this research, the 2020 UN World Water Report does explicitly relate water insecurity and intersectionality, especially regarding race and class ( UN Water, 2020). Peer-reviewed studies on this issue, however, overwhelmingly exist in the North American context (e.g., Deitz and Meehan, 2019;Dickin and Gabrielsson, 2023;Harrington et al, 2023;Meńdez-Barrientos et al, 2023;Workman and Shah, 2023). For example, a spatial analysis of water insecurity across the United States by Deitz and Meehan (2019) found that deficiencies in household water infrastructure are concentrated in regions typically inhabited by racialized groups.…”
Section: The Role Of Colonialism and Race In Marine Ecotourism And Wa...mentioning
confidence: 99%